2017
DOI: 10.1177/1934578x1701200832
|View full text |Cite
|
Sign up to set email alerts
|

A New Diphenyl Ether Glycoside from Xylosma longifolium Collected from North-East India

Abstract: A new diphenyl ether glycoside, xylosmaloside (1), was isolated from the MeOH extract of Xylosma longifolium Clos. The structure of xylosmaloside (1) was elucidated using MS analyses, extensive 2D-homo and heteronuclear NMR data interpretation and the chemical conversions. Xylosmaloside (1) showed stronger antioxidant activity than ascorbic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Compounds 39 – 45 were confirmed as sugar molecules from comparison of their deprotonated ion mass and fragmentation behaviors with those reported in the literature and online databases [ 47 , 48 , 65 , 66 , 67 , 69 ]. Maltitol, one of the sugar molecules, inhibits Streptococcus mutans DMST 18777, and xylosmaloside has greater antioxidant properties than ascorbic acid [ 70 , 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compounds 39 – 45 were confirmed as sugar molecules from comparison of their deprotonated ion mass and fragmentation behaviors with those reported in the literature and online databases [ 47 , 48 , 65 , 66 , 67 , 69 ]. Maltitol, one of the sugar molecules, inhibits Streptococcus mutans DMST 18777, and xylosmaloside has greater antioxidant properties than ascorbic acid [ 70 , 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fresh leaves and stem bark extracts are used for ringworm, acne and scabies. The boiled and brewed leaves of this plant are used for curing fever, tuberculosis, inflammation and bronchial disorder [35] . In Ayurveda system of medicine, it is used as an active herb for treatment of insomnia due to its sedative and central nervous system stimulant properties [36] .…”
Section: Botanical Descriptionmentioning
confidence: 99%
“…Several studies reported the presence of active chemical constituents such as glycosides, triterpenoids, flavonoids, sterols, fatty acid and others in different parts of X. longifolia [35,16,[38][39][40] . However, glycoside, triterpenoids, flavonoids, fatty acids and sterols were the main classes of secondary metabolites [16,35,39,41] . The glycosides namely, xylosmaloside was isolated from whole plant [35] whereas xylongoside A and xylongoside B from stem bark of X. longifolia [39] .…”
Section: Phytochemistrymentioning
confidence: 99%
See 2 more Smart Citations